Reverse total shoulder glenoid component inclination affects glenohumeral kinetics during abduction: a cadaveric study - Knighton, Tyler W.; Chalmers, Peter N.; Sulkar, Hema J.; Aliaj, Klevis; Tashjian, Robert Z.; Henninger, Heath B. (Journal of shoulder and elbow surgery, 2022)
Optimal implant placement in reverse total shoulder arthroplasty (rTSA) remains controversial. Specifically, the optimal glenoid inclination is unknown. Therefore, a cadaveric shoulder simulator with 3-dimentional human motion specific to rTSA was used to study joint contact and muscle forces as a function of glenoid component inclination. Eight human cadaver shoulders were tested before and after rTSA implantation. Scapular plane abduction kinematics from control subjects and those with rTSA drove a cadaveric shoulder simulator with 3-dimentional scapulothoracic and glenohumeral motion. Glenoid inclination varied from −20° to +20°. Outputs included compression, superior-inferior (S/I) shear, and anterior-posterior shear forces from a 6° of freedom load cell in the joint, and deltoid and rotator cuff muscle forces. Data were evaluated with statistical parametric mapping and t-tests. Inferior glenoid inclination (−) reduced S/I shear by up to 125% relative to superior inclination, with similar compression to the neutral condition (0°). Superior inclinations (+) increased the S/I shear force by approximately the same magnitude, yet decreased compression by 25% in the most superior inclination (+20°). There were few differences in deltoid or rotator cuff forces due to inclination. Only the middle deltoid decreased by approximately 7% for the most inferior inclination (−20°). Compared with native shoulders, the neutral (0°) rTSA inclination showed reduced forces of 30%-75% in the anterior deltoid and a trend toward decreased forces in the middle deltoid. Force demands on the rotator cuff varied as a function of elevation, with a trend toward increased forces in rTSA at peak glenohumeral elevation. Inferior inclination reduces superior shear forces, without influencing compression. Superior inclination increased S/I shear, while decreasing compression, which may be a source of component loosening and joint instability after rTSA. Inferior inclination of the rTSA glenoid may reduce the likelihood of glenoid loosening by reducing the magnitude of cyclic shear and compressive loading during arm elevation activities, although this may be altered by specific-subject body habitus and motion. These factors are especially important in revision rTSA or glenoid bone grafting where there is already a 3-fold increase in glenoid baseplate loosening vs. primary rTSA.